Making the Best of a Bad Situation: Case Report of a Nonreplantable Four-finger Amputation with Flap Coverage and Partial Hand Prosthesis Utilization. Issue 4 (13th April 2022) - Graham, Emily M.; Arbon, Jantz; Baschuk, Christopher M.; Duncan, Adam; Mendenhall, Shaun D.
Abstract : Summary: Partial hand amputations (PHAs) are often associated with detriments to self-expression, independence, and employment. Modern partial hand prostheses, coupled with reconstructive surgery, may greatly mitigate the physical, psychological, social, and financial impairments caused by PHAs. The MCPDriver is a body-powered prosthesis and is an example of one of these modern, easy-to-use prostheses. This case report describes a 30-year-old man who experienced a traumatic, nonreplantable four finger degloving amputation of digits 2–5 at the level of the proximal phalanges. Initial reconstruction included preserving the length of the amputated phalanges and using a pedicled groin flap for soft tissue coverage with the goal to ultimately facilitate the use of a partial hand prosthesis. Once the PHA was stable, the multidisciplinary hand team held several discussions to review how to revise the flap for an MCPDriver. Staged debulking surgeries and syndactyly releases facilitated a successful fitting with the prosthesis. The patient resumed employment and bimanual tasks shortly after being fit with the prosthesis. The patient also reported significant improvements in his mental health and in the quality of his social interactions. This case illustrates how reconstructive surgeries coupled with partial hand prosthesis utilization can restore form and function following amputation. Familiarity with the modern classes of upper extremity prostheses and collaborating within a multidisciplinary hand team will likely enhance reconstructive outcomes following traumatic PHAs.